2022
DOI: 10.1097/sla.0000000000005539
|View full text |Cite
|
Sign up to set email alerts
|

Defining Benchmark Outcomes for Distal Pancreatectomy

Abstract: Objective: Defining robust and standardized outcome references for distal pancreatectomy (DP) by using Benchmark analysis. Background: Outcomes after DP are recorded in medium or small-sized studies without standardized analysis. Therefore, the best results remain uncertain. Methods: This multicenter study included all patients undergoing DP for resectable benign or malignant tumors in 21 French expert centers in pancreas surgery from 2014 to 2018. A low-risk cohort defined by no significant comorbidities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“… 6 , postoperative safety outcomes from the current meta-analysis appear within benchmark cut-offs. Recently published analyses further report benchmark criteria for minimally invasive and open DP 38 , 43 , 44 . Benchmark cut-off values for mortality rate in PD were set at less than or equal to 1.6 per cent and 2 per cent by Sánchez-Velázquez et al .…”
Section: Discussionmentioning
confidence: 99%
“… 6 , postoperative safety outcomes from the current meta-analysis appear within benchmark cut-offs. Recently published analyses further report benchmark criteria for minimally invasive and open DP 38 , 43 , 44 . Benchmark cut-off values for mortality rate in PD were set at less than or equal to 1.6 per cent and 2 per cent by Sánchez-Velázquez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hospital readmission is currently considered a measure of health care quality in patients undergoing pancreatectomy. 31,32 Two recent studies that focused on the benchmark analysis of PD and DP considered hospital readmission as a metric to define the best postoperative outcomes. However, some authors have reported that readmission may not always correlate with the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, benchmarks have already been established for breast 3 , liver [4][5][6][7][8] , oesophageal 9 , and pancreatic [10][11][12][13] surgery. For pancreatic surgery, benchmarks have only been applied to open pancreatoduodenectomy 10,11 , open distal pancreatectomy 12 or minimally invasive distal pancreatectomy with splenectomy 13 , and none have been defined for spleen-preserving distal pancreatectomy (SPDP).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, benchmarks have already been established for breast 3 , liver [4][5][6][7][8] , oesophageal 9 , and pancreatic [10][11][12][13] surgery. For pancreatic surgery, benchmarks have only been applied to open pancreatoduodenectomy 10,11 , open distal pancreatectomy 12 or minimally invasive distal pancreatectomy with splenectomy 13 , and none have been defined for spleen-preserving distal pancreatectomy (SPDP). As previous comparative studies [14][15][16][17][18] between distal pancreatectomy with and without splenectomy have reported significant differences in intraoperative and postoperative outcomes, separate benchmarks are required for the two procedures.…”
Section: Introductionmentioning
confidence: 99%